Preliminary design of an OWC wave energy converter battery charger (Proceedings of the European Wave and Tidal Energy Conference, 2023)
This paper introduces a low-power off-grid oscillating water column wave energy converter with an internal battery bank. The research aims at the preliminary design and devising of the control strategy of a power electronics interface between the turbo generator and the battery bank. The converter comprises a spar buoy, a biradial turbine, a permanent magnet generator, a full-wave bridge rectifier, a braking chopper, a DC-to-DC step-down converter, and a lead-acid battery bank. The power-take-off system was modelled in Simulink/MATLAB, and its performance was assessed with steady-state simulations, considering a wave climate characteristic of Leixões, Portugal. The chamber pressure, the turbine, generator and rectifier performance were taken from experimental data sets. A simple battery model was derived from the manufacturer's datasheet. An ideal step-down DC-to-DC converter operating in discontinuous conduction mode regulates the battery charging current. This converter, in parallel with the braking chopper, adjusts the generator counter torque by regulating the current through the rectifier. Twelve system variables were recorded for selected pairs of input pressure and step-down converter design coefficient. The power at the rectifier's output terminals was mapped for the rotational speed and input pressure. The results show a system rating of 1.4 kW with 400 W of electrical power at 200 rad/s for the most frequent sea states. The range of the duty cycle, the inductance and the braking resistance were derived. Two closed-loop controllers were proposed for managing the step-down converter and the braking chopper. Their set points and saturation limits were derived from the simulation results.